Bringing Home Baby Euclid: Testing Infants’ Basic Shape Discrimination Online - Bochynska, Agata; Dillon, Moira R. (Frontiers in Psychology, 2021)
Online developmental psychology studies are still in their infancy, but their role is newly urgent in the light of the COVID-19 pandemic and the suspension of in-person research. Are online studies with infants a suitable stand-in for lab-based studies? Across two unmonitored online experiments using a change-detection looking-time paradigm with 96 7-month-old infants, we found that infants did not exhibit measurable sensitivities to the basic shape information that distinguishes between 2D geometric forms, as had been observed in previous lab experiments. Moreover, while infants were distracted in our online experiments, such distraction was nevertheless not a reliable predictor of their ability to detect shape information. Our findings suggest that the change-detection paradigm may not elicit infants’ shape discrimination abilities when stimuli are presented on small, personal computer screens: Stimuli may not be perceived as two discrete events with only one event displaying uniquely changing information that draws infants’ attention. Some developmental paradigms used with young infants, even those that seem well-suited to the constraints and goals of online data collection, may thus not yield results consistent with lab results that rely on highly controlled settings and specialized equipment, such as large screens. As developmental researchers continue to adapt lab-based methods to online contexts, testing those methods online is a necessary first step in creating robust tools and expanding the space of inquiry for developmental science conducted online.